2017
DOI: 10.1016/j.ins.2016.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Clustering coefficients of large networks

Abstract: Let G be a network with n nodes and eigenvalues λ 1 ≥ λ 2 ≥ · · · ≥ λ n . Then G is called an (n, d, λ)We show that this description also holds for strongly regular graphs and Erdős-Rényi graphs. Although most real-world networks are not theoretically constructed, we find that, interestingly, many of them have c(G) close to d/n, and many close to 1 − µ2(n−d−1) d (d−1) , where d is the average degree of G, and µ 2 is the average of the numbers of common neighbors over all non-adjacent pairs of nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…Many large-scale networks have special forms of clustering coefficients, although the degree varies. Li et al [32] showed that the average clustering coefficient of the network with large degree accords with asymptotic expression. This provides a new research guide for our next research work.…”
Section: Comparison With Representation Learning Methodsmentioning
confidence: 89%
“…Many large-scale networks have special forms of clustering coefficients, although the degree varies. Li et al [32] showed that the average clustering coefficient of the network with large degree accords with asymptotic expression. This provides a new research guide for our next research work.…”
Section: Comparison With Representation Learning Methodsmentioning
confidence: 89%
“…In addition, some research on complex social networks is also used in the field of social recommendation. In these studies, the features of the small world [27] and the clustering coefficients [28] in complex networks are exploited to mine the sociality among users and predict the preferences of target users. For instance, Liu G et al [29] designed an innovative heuristic path mining model based on multiple forecasts that utilized the influence of complex social networks to optimize the user social paths.…”
Section: Related Workmentioning
confidence: 99%
“…A distinctive feature of several complex networks (including social ones) is an high density of 'triangles', namely triples of nodes any two of which are linked. Such a density is measured in terms of a [0,1]-ranged ratio by the so-called clustering coefficient, which is in fact the probability that by picking at random a vertex and two of its neighbors these latter are also neighbors of each other [20], [28]. A cluster score function can thus be conceived to measure the density of triangles locally, namely in the subgraphs spanned by vertex subsets.…”
Section: Weights and Common Neighborsmentioning
confidence: 99%
“…In network analysis cc(G) is a key indicator measuring 'transitivity', namely to what extent sharing some common neighbor entails being adjacent, for any two vertices. While in social networks the clustering coefficient is higher than in non-social ones [28], several complex networks display the same asymptotic clustering coefficient as certain strongly regular graphs, in contrast to small-world networks [6], [20]. Now consider the aim to assign scores v(A) to clusters A in a way such that higher values of the clustering coefficient cc(G(A)) over spanned subgraphs provide greater scores.…”
Section: B Score Of Pairs and Common Neighborsmentioning
confidence: 99%